Hypopituitarism and Legg-Calve-Perthes disease related to difficult delivery - Veysel Nijat Baş; Salih Uytun; Ümit Erkan Vurdem; Yasemin Altuner Torun (Korean Pediatric Society, 2015)
Legg-Calve-Perthes (LCP) disease is characterized by idiopathic avascular osteonecrosis of the epiphysis of the femur head. The main factor that plays a role in the etiology of the disease is decreased blood flow to the epiphysis. Many predisposing factors have been suggested in the etiology of LCP disease, and most have varying degrees of effects. Here we present the case of a boy aged 4 years and 10 months with complaints of short stature and a diagnosis of multiple hypophyseal hormone deficiency, in whom LCP disease and difficult birth-related pituitary stalk interruption syndrome were identified by anamnesis. The present case revealed that LCP disease and hypophyseal hormone deficiency could be secondary to difficult birth and that LCP disease could be secondary to insulin-like growth factor 1 deficiency. Additionally, to the best of our knowledge there is no published case on the relation between LCP disease and insulin-like growth factor 1 deficiency. Therefore, we believe that this case is worthy of presentation.